Predictors of treatment utilization and barriers to treatment utilization among individuals with lifetime cannabis use disorder in the United States. (1st December 2017) - Kerridge, Bradley T.; Mauro, Pia M.; Chou, S. Patricia; Saha, Tulshi D.; Pickering, Roger P.; Fan, Amy Z.; Grant, Bridget F.; Hasin, Deborah S.
Highlights: Little is known about predictors/barriers of cannabis-specific treatment utilization. Preference for self-reliance and fear of stigma were barriers to cannabis use disorder (CUD) treatment. Presence of withdrawal and severity of CUD were predictors of CUD treatment. Programs to reduce stigma and increase awareness of CUD treatment are needed. Abstract: Objective: To present information on predictors of treatment utilization and barriers to treatment utilization among individuals with lifetime DSM-5 cannabis use disorder (CUD). Method: Face-to-face survey of a representative sample of the adult US general population (n = 36, 309). Results: Treatment rates for CUD were low in this general population survey (13.7%). Severity of CUD and comorbidity of other lifetime drug use disorders were significant predictors of lifetime treatment utilization for CUD. Preference for self-reliance, minimizing problems, fear of stigma, and financial and structural issues were among the most frequently endorsed reasons for respondents not seeking treatment when they perceived the need for treatment among individuals with lifetime CUD, regardless of whether they eventually utilized treatment at some time in their lives. Conclusions: Given the rising prevalence of CUD in the US over the past decade and currently low treatment rates for CUD, increased provision for services for CUD appears critically needed, especially those that screen for and treat, when present, other drug use disorders. Programs to reduce stigma and financial barriers are needed, as well as programs to increase awareness among the general public, health care professionals about the nature and seriousness of CUD, and the availability and effectiveness of treatment for this disorder.